Implementation of the Campus Teaching Program in Improving Students Literacy at State Elementary School 2 Eromoko - Astri Noviandari, Bella; Aris Rahmadani, Ni Kadek (Universitas Negeri Semarang, 2025)
The teaching campus is part of the implementation of the Independent Campus policy whose program is very strategic for students with the Teaching Campus Program providing students who can help develop learning, especially in increasing literacy competency and learning innovation. This study aims to: 1) determine the implementation of literacy in the campus teaching program batch 3 at SD Negeri 2 Eromoko. 2) determine the obstacles and solutions in overcoming the obstacles in implementing literacy in the campus teaching program batch 3 at SD Negeri 2 Eromoko. This study uses a mix method approach with a case study design. The subjects of this study were teachers of grades II, III, and IV, students of SD Negeri 2 Eromoko. Data collection techniques with observation, interviews, and documentation. The validity of the data used is source triangulation. Data analysis with reduction, data presentation, drawing conclusions/verification. The results of the study showed that the implementation of campus teaching students related to literacy at SD Negeri 2 Eromoko was based on the habituation stage, development stage, and learning stage resulted in significant changes in student literacy. The obstacles faced at Eromoko 2 Public Elementary School are students' poor reading habits, inadequate facilities and infrastructure, and students' lack of motivation to read books.